การพัฒนาชุดการทดลองเซลล์กัลวานิกแบบย่อส่วนและต้นทุนต่ำเพื่อใช้เป็นอุปกรณ์ในการสอนเคมีไฟฟ้า - Khattiyavong, Phetvilay; Jarujamrus, Purim; Supasorn, Saksri; Kulsing, Chadin (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2014)
The Development of Small Scale and Low-Cost Galvanic Cells as a Teaching Tool for Electrochemistry Phetvilay Khattiyavong, Purim Jarujamrus , Saksri Supasorn and Chadin Kulsing รับบทความ: 19 กันยายน 2557; ยอมรับตีพิมพ์: 19 พฤศจิกายน 2557 บทคัดย่อ งานวิจัยนี้ได้พัฒนาเซลล์กัลวานิกแบบย่อส่วนและต้นทุนต่ำ มีวิธีการสร้างที่ง่าย เพื่อใช้เป็นอุปกรณ์สำหรับการสอนเคมี ไฟฟ้าในระดับมัธยมศึกษาตอนปลาย การออกแบบครั้งนี้ใช้แนวคิดเคมีรักษ์สิ่งแวดล้อมคือ ลดปริมาณการใช้สารเคมี ทำให้ของเสียจากสารเคมีมีปริมาณน้อยลง และใช้เวลาในการทดลองน้อยลง แต่ยังคงรักษาภาวะที่สมบรูณ์ของการทดลองไว้ได้อย่างต้นแบบ ในงานวิจัยนี้พัฒนาเซลล์กัลวานิกที่ประกอบด้วยขั้วไฟฟ้า Cu Zn Al Mg และ Fe สะพานเกลือทำมาจากเส้นด้ายชนิดฝ้ายราคาถูก (ยาว 18 เซนติเมตร) ชุบด้วยสารละลายอิเล็กโทรไลต์ อุปกรณ์ที่พัฒนาขึ้น มีความสอดคล้องกับการทดลองแบบเดิม แต่ใช้ปริมาตรสารละลายอิเล็กโทรไลต์น้อยลง (2.00 มิลลิลิตร) จากการศึกษาพบภาวะที่เหมาะสมดังต่อไปนี้ ความเข้มข้นของสาร ละลายอิเล็กโทรไลต์ที่เหมาะสมของแต่ละเซลล์ (0.01 โมลต่อลิตร) สารละลายที่ใช้ชุบสะพานเกลือ (โพแทสเซียมไนเทรต ความเข้มข้น 0.01 โมลต่อลิตร) และศึกษาอายุการใช้งานของสารละลายอิเล็กโทรไลต์ในภาวะที่เหมาะสม (720 ชั่วโมง) ผลการทดลองที่ได้จากการสร้างเซลล์กัลวานิกเปรียบเทียบกับวิธีแบบเก่า เมื่อใช้ t-test ทดสอบศักย์ไฟฟ้าของวิธีทั้งสองไม่มีความแตกต่างกันอย่างมีนัยสำคัญ (tstat = 2.414, tcritical = 2.447) ที่ระดับความเชื่อมั่นร้อยละ 95 การวิเคราะห์คะแนนก่อนเรียนและหลังเรียนของนักเรียน (ก่อนและหลังการใช้เซลล์ที่พัฒนาขึ้น ตามลำดับ) พบว่า มีผลสัมฤทธิ์ทางการเรียนเฉลี่ยก่อนเรียนและหลังเรียนมีค่าเท่ากับ 4.69 และ 8.15 ตามลำดับ โดยมีร้อยละความแตกต่างสำหรับคะแนนก่อนเรียนและหลังเรียนเท่ากับร้อยละ 34.89 ค่าสัมประสิทธิ์การกระจายตัวมีค่าเท่ากับร้อยละ 24.09 และ 15.82 สำหรับคะแนนก่อนเรียนและหลังเรียนตามลำดับ เมื่อใช้ t-test แบบกลุ่มตัวอย่างไม่อิสระต่อกันทดสอบคะแนนของการสอบทั้งสองครั้ง พบว่า มีความแตกต่างกันอย่างมีนัยสำคัญ (tobserved = 9.55, tcritical = 2.07) ที่ระดับความเชื่อมั่นร้อยละ 95 นอกจากนี้นักเรียนยังมีความเข้าใจที่เพิ่มมากขึ้นต่อการทดลองเซลล์กัลวานิกแบบย่อส่วนและต้นทุนต่ำ วิธีการนำเสนอนี้คาดว่าจะเป็นเครื่องมือในการสอนที่มีประสิทธิภาพและมีประโยชน์ในการศึกษาระดับมัธยมศึกษาตอนปลาย คำสำคัญ: การทดลองแบบย่อส่วน เซลล์กัลวานิก สะพานเกลือ โรงเรียนมัธยมศึกษาตอนปลาย Abstract A simple method for construction of small-scale and low-cost galvanic cells was developed as a teaching tool for electrochemistry of high school students. The method was designed based on the concept of “Green chemistry” reducing use of chemicals, less waste generation, and time consumption while retaining the experimental concepts. The galvanic cells contain various electrodes, including Cu, Zn, Al, Mg and Fe, and a low cost salt bridge which was made from a cotton thread (with the length of 18 cm) soaked with electrolyte solutions. Our experimental setup corresponded to the conventional platform; but with lesser use of electrolyte solution (2.00 mL). The cells were studied for the optimum conditions including concentration of electrolyte of each cell (0.01 M), the solutions employed as salt bridge (0.01M KNO3) as well as the study of reagent lifetime of electrolyte (720 h). The results obtained from the constructed galvanic cells were compared to those from the galvanic cells developed through conventional method. According to the t-test, the cell potential values obtained from both methods were comparable (tstat = 2.414, tcrictical = 2.447) at p= 0.05. The analysis of pre-test and post-test scores of the students (before and after using the developed cells, respectively) was also performed revealing the mean values of 4.69 and 8.15, respectively, with the difference of mean percentage for the pre-test and post-test scores being 34.89%. CV (coefficient variation) was 24.09% and 15.82% for the pre-test and post-test, respectively. According to the paired-samples t-test analysis, the scores of the two examinations were significantly different (tobserved = 9.55, tcritical = 2.07) at p=0.05. The improved post-test scores obtained from the students indicate their increased understanding towards the small scale and low cost galvanic cells. The approaches presented herein are expected to be cost-effective and useful teaching tool incorporated into high school education. Keywords: Small scale, Galvanic cell, Salt bridge, High school